Sosialiasi Pendidikan, Program Indonesian Pinntar (PIP) Dan KIP-Kuliah Didesa Wringintelu Kecamatan Puger Kabupaten Jember Tahun 2023 - Mustofa , Mustofa; Aditya Nugraha , Raafi; Sulastri , Sulastri; Abdul Gufron, Shehona (Institut Teknologi dan Sains Mandala, 2023)
Education is very important for human life, because with education we get knowledge and experience in every process. He also said,